Scenario simulation of indoor post-earthquake fire rescue based on building information model and virtual reality. (May 2020) - Lu, Xinzheng; Yang, Zhebiao; Xu, Zhen; Xiong, Chen
Highlights: A framework for VR scenario modeling of post-earthquake indoor fires is proposed. The combination of multiple hazards is considered in the fire rescue scenario. Volume rendering and particle system are employed to visualize smoke. Smoke has more significant influence on fire rescue compared with fallen debris. Abstract: Post-earthquake fires occur frequently, and the seismic damage to non-structural components results in dangerous fire and evacuation environments. Both firefighters and trapped people will face serious threats to life during the rescue. Consequently, a simulation framework of an indoor post-earthquake fire rescue scenario based on building information model (BIM) and virtual reality (VR) is proposed herein. Information of structural and non-structural components is extracted from the BIM. Subsequently, the seismic damage of non-structural components is predicted according to the time-history results and fragility curves. Moreover, a smoke visualization method combining volume rendering and the particle system is also proposed. A case study of a 19-story hospital is conducted using the proposed method for establishing the fire rescue scenario. The results show that the established VR scenario has high realism and smooth interactivity, and the influence of smoke on the fire rescue is more significant than that of fallen debris.